The Chromosome-Level Genome Assembly of European Grayling Reveals Aspects of a Unique Genome Evolution Process Within Salmonids. Issue 5 (1st May 2019) - Sävilammi, Tiina; Primmer, Craig R; Varadharajan, Srinidhi; Guyomard, René; Guiguen, Yann; Sandve, Simen R; Vøllestad, L Asbjørn; Papakostas, Spiros; Lien, Sigbjørn
Abstract: Salmonids represent an intriguing taxonomical group for investigating genome evolution in vertebrates due to their relatively recent last common whole genome duplication event, which occurred between 80 and 100 million years ago. Here, we report on the chromosome-level genome assembly of European grayling ( Thymallus thymallus ), which represents one of the earliest diverged salmonid subfamilies. To achieve this, we first generated relatively long genomic scaffolds by using a previously published draft genome assembly along with long-read sequencing data and a linkage map. We then merged those scaffolds by applying synteny evidence from the Atlantic salmon ( Salmo salar ) genome. Comparisons of the European grayling genome assembly to the genomes of Atlantic salmon and Northern pike ( Esox lucius ), the latter used as a nonduplicated outgroup, detailed aspects of the characteristic chromosome evolution process that has taken place in European grayling. While Atlantic salmon and other salmonid genomes are portrayed by the typical occurrence of numerous chromosomal fusions, European grayling chromosomes were confirmed to be fusion-free and were characterized by a relatively large proportion of paracentric and pericentric inversions. We further reported on transposable elements specific to either the European grayling or Atlantic salmon genome, on the male-specific sdY gene in the European grayling chromosome 11A, and on regions under residual tetrasomy in the homeologous European grayling chromosome pairs 9A-9B and 25A-25B. The same chromosome pairs have been observed under residual tetrasomy in Atlantic salmon and in other salmonids, suggesting that this feature has been conserved since the subfamily split.